Biochar soil application induces stress tolerance in Arachis hypogaea L. Varieties inoculated with stem rot fungus (Athelia rolfsii (Sacc.) C.C. Tu & Kim.) - Okon, O. G.; Uwaidem, Y. I.; Antia, U. E.; Archibong, B. F.; Okon, J. E. (Journal of Plant Stress Physiology, 2025)
This study aims to investigate the extent to which soil amendment with biochar can promote growth and induce biotic stress tolerance in Arachis hypogaea accessions (TAH-183, TAH-142, TAH-164, TAH-124 and TAH-134) inoculated with stem rot fungus (Athelia rolfsii). The experiment was set up in a complete block design. 5 seeds of A. hypogaea accessions were planted in 10 kg of sterilized soil in triplicates (control(C), A. rolfsii alone (T) and A. rolfsii+Biochar (A+T). Characterized pathogen A. rolfsii causing vine rot and wilt disease was obtained from Botany pathology laboratory and spawned with 300 g of millet seeds. 5 g of A. rolfsii colonized seeds were used to infect A. hypogaea accessions seedlings. Growth parameters and disease severity index (DSI) were taken using standard methods, while the total photosynthetic pigments (TPP) were determined using the atLeaf chlorophyll meter. All A. hypogaea accessions showed 100% germination across all treatments after 11 days except TAH-183 (80%) and TAH-134 (60%). TAH-142 and TAH-183 accessions inoculated with A. rolfsii were the most susceptible with disease severity index of 50% and 33.30% respectively. However, biochar application treatments recorded 0% DSI for all accessions. At 6 weeks after planting (WAP), it was observed that inoculation of A. hypogaea accessions with A. rolfsii significantly (p<0.001) reduced the growth parameters such as shoot length for TAH-142 and TAH-124 which recorded the lowest values; T=3.40±181 cm, C=15.50±1.45 cm, A+T=20.00±1.70 cm; and T=8.33±2.33 cm, C=15.20±1.20 cm, A+B=21.12±1.90 cm while TAH-183 and TAH-164 had the highest shoot growth (T=19.33±1.36 cm, C=20.00±1.54 cm, A+T=24.77±1.67 cm; T=16.83±1.76 cm, 17.00±1.13 cm, A+T=28.30±2.00 cm) when compared to their controls and biochar treatments. TAH-142 (T=30.00 mg/kg, C=37.90 mg/kg, A+B=40.00 mg/kg) recorded the least TPP contents, while TGM-183 (T=36.00 mg/kg, C=40.10 mg/kg, A+T=44.50 mg/kg) recorded the highest TPP. For postharvest parameters; TAH-142 (5.77±0.09 g) had the lowest fresh biomass yield while TAH-164 (58.70±1.56 g) had a better tolerance to A. rolfsii infection. However, TAH-183 showed greater fresh biomass yield when biochar was applied (89.67±4.53 g) while TAH-142 recorded the lowest (78.90±2.21 g). Amelioration of soil with biochar significantly (p=0.001) stimulated growth above the treatment and control. Similar trend was observed for leaf area, petiole length, leaf number, stem girth and internode length. This study has shown that A. rolfsii infection had a negative effect on the growth and biomass yield of A. hypogaea and soil amended with biochar conferred disease tolerance in all A. hypogaea accessions thus eliminating the need for the use of fungicides and additional fertilizer application.